Progressive Islamic Teaching and Learning: Integrating Knowledge and Practice for Societal Advancement - Dzulfikar Akbar Romadlon; Istikomah Istikomah; Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2023)
This conceptual study explores the paradigm of progressive Islamic teaching and learning, addressing the disconnection between traditional teachings and modern science, which hinders their societal relevance. Fueled by the